TERANG DAN KEGELAPAN: PERAN PENDIDIKAN AGAMA KRISTEN MENUNTUN GENERASI ALPHA BERDASARKAN MAZMUR 119:105 - Yafarman Zai; Salmon Wompere (THEOSOPHIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Generation Alpha is a generation group born and developed amidst the rapid advancement of the digital world, where technological developments, globalization, and information flow very quickly. This situation makes this generation superior in mastering technology, but at the same time faces them with serious challenges, such as moral and spiritual crises, and loss of identity. This study aims to describe the role of Christian Religious Education (PAK) in guiding Generation Alpha to live under the light of God's word as stated in Psalm 119:105, "Your word is a lamp to my feet and a light to my path." The research method applied is descriptive, qualitative, by examining biblical texts, Christian educational theories, and the distinctive characteristics of Generation Alpha. The research findings show that PAK has an important and strategic role in helping Generation Alpha distinguish between the path of light and the path of darkness in their lives. First, PAK places God's word as a guide for life in the midst of a digital world filled with the influence of secularism and moral relativism. Second, Christian Education (PAK) serves to shape Christian character rooted in love, honesty, discipline, and social concern, so that this generation is not only intellectually superior but also spiritually mature. Third, PAK strengthens the defense of faith, so that Generation Alpha can face the negative impacts of technology and remain steadfast in Christ. Fourth, PAK guides them to be a light to others, by displaying God's love and truth in their daily lives in the modern world. Thus, it can be concluded that PAK plays a crucial role in guiding Generation Alpha so that they do not fall into the darkness of the digital age, but rather live as bearers of Christ's light. God's Word needs to be applied concretely in all aspects of education and life, so that Generation Alpha can develop into a generation steadfast in faith, with Christ-like character, and able to positively influence their environment.